Analysis Of The Use Of Low-Cost Strategy For Smes In Indonesia In Covid Pandemic-19 - Aprilia NingrumAmbarwati; Setyo Riyanto (Syntax Corporation Indonesia, 2020)
The Coronavirus that was present in the midst ofa society in 2020 really caught the attention. The visible impact not only affects public health but also affects the economy and MSMEs not only in Indonesia but also in various countries. Because of its spread that is too fast then in a number of countries to close the area, which resulted in the difficulty of export and import goods, therefore MSMEs who were previously able to get goods from out of town finally only got goods in Indonesia. This topic will discuss the use of low-cost strategies in MSMEs, especially in Indonesia. The research method used is a descriptive research and based on the results of the questionnaire. And the results of this study indicate that during this pandemic period, consumers are looking for relatively low prices. This is evidenced by the use of the low-cost strategy at MSMEs in this pandemic era.